Social Accounting in Social Justice Morality in Islamic Banks - Istanti, Enny; Andrianto, Andrianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Social issues such as poverty, wealth distribution, and social justice remain critical concerns in many countries. Specific Background: In this context, Islamic banks, particularly the 22 institutions operating in Southeast Asia, have the potential to apply social justice principles in their interactions with local communities. Knowledge Gaps: While previous studies have examined the commercialisation of Islamic banking, research exploring how these institutions integrate social justice into their operations is limited. Objectives: This study aims to investigate the social accounting practices of Islamic banks, focusing on disclosures that reflect a commitment to social justice. Methods: Using a qualitative approach, this study analyses data from annual reports and official websites to evaluate how Islamic banks implement social justice in the communities they serve. Results: The findings show that these banks seek to align their disclosures with Islamic spiritual and moral teachings, demonstrating an underlying narrative that emphasises ethical accountability and religious conformity. Novelty: This study contributes to the limited literature bridging Islamic religious values and the pursuit of social goals in financial institutions. Implications: A focus on the misalignment between religious values and banking ethics opens up opportunities for reform among Islamic banks and encourages deeper engagement from stakeholders concerned with ethical financial practices.